The Effects of Jieduquyuzishen Prescription-Treated Rat Serum on the BAFF/BAFF-R Signal Pathway - Wu, De-hong (PLoS One, 2015)
Systemic lupus erythematosus (SLE) is a chronic inflammatory disease mainly characterized by B cell hyperactivity. Glucocorticoid (GC) is widely used in SLE for its potent anti-inflammatory and immunosuppressive effects. Despite its important clinical efficacy, high-dose or long-term use of GC can cause severe side effects, such as osteoporosis, osteonecrosis, cataracts, hyperglycemia, coronary heart disease and cognitive impairment. Our early clinical studies have shown that Jieduquyuzishen prescription (JP) can effectively reduce the adverse effects and improve the curative effect of GC in the treatment of SLE. The BAFF/BAFF-R signaling pathway plays an important role in the development of SLE and has been regarded as a potential target for the therapy of SLE. In this study, we attempt to investigate the effect of JP on the BAFF/BAFF-R signaling pathway to explore the mechanism of JP in reducing the toxicity and enhancing the efficacy of GC. YAC-1 cells, isolated rat peripheral blood lymphocytes, polymorphonuclear neutrophils and spleen lymphocytes were treated with drug-containing serum. The results of RT-PCR, Western blot and dual-luciferase reporter gene assays indicate that either JP or GC can inhibit the mBAFF-induced up-regulation of BAFF, BAFF-R, Bcl-2, IL-10 and NF-κB in YAC-1 cells and WEHI-231 cells. Furthermore, MTS, flow cytometry and CFSE results reveal that the proliferation and survival of lymphocytes activated by mBAFF are suppressed by JP, GC and their combination. Contrary to GC, JP can reduce the apoptosis and raise the survival of polymorphonuclear neutrophils and can’t increase the apoptosis of the peripheral blood lymphocytes and spleen lymphocytes. Therefore, it is possible that JP can down-regulate the BAFF/BAFF-R signaling pathway as effectively as GC, which may result in the dosage reduction of GC, thus decreasing the toxicity and improving the efficacy of GC-based treatment of SLE.